ISOLATION OF COMMON CARP b-ACTIN PROMOTER - Hidayani, A.A -; Carman, O. -; Alimuddin - (Bionatura, 2013)
Promoter in the transgene construct plays an importantrole on regulating of transgene expression levelin transgenic fish. In fish transgenesis, researcherconvinced that use all-fish promoter more safetyand prospective. This study was performed to isolateâ-actin promoter, - the promoter which has ubiquitous,constitutive, house keeping characteristics, fromcommon carp. -actin promoter from common carp(ccBA) was isolated using PCR method with FBP1,RBP1 and RBP2 primers. Sequencing was performedusing ABI PRISM 3100 machine and analysis ofsequences was conducted using GENETYX version 7software. The results of sequence analysis showed thatthe length of DNA fragment obtained approximately1,5 kb and containing the evolutionary conservedsequences of transcription factor for â-actin promoterincluding CCAT, CArG and TATA box. The resultsdemonstrated that isolated sequence was a commoncarp â-actin promoter.Key words: Homologous promoter, GFP, carp transgenic